O11.3 Extreme heterogeneity in vaginal microbial kinetics within and across women. (8th July 2017) - Schiffer, Joshua; Srinivasan, Sujatha; Lopez, A; Wang, L; Proll, Sean; Yuhas, K; Hughes, JP; Wald, Anna; Fredricks, DN
Abstract : Introduction: Incident bacterial vaginosis (BV) is associated with a shift in the vaginal microbiota from lactobacillus predominant to a diverse community of anaerobic bacteria The kinetics of this shift are poorly described. We sought to identify the dynamics of incident BV. Methods: Twenty women with frequent BV (>3 episodes per year) self-collected vaginal swabs every 8 hours for 60 days. Swabs were analysed with quantitative PCR targeting Lactobacillus iners, Lactobacillus jensenii, Lactobacillus crispatus, Gardenerella vaginalis, Atopobium vaginae, bacterial vaginosis associated bacterium-2 (BVAB2), and Megasphaera spp . We defined bacteria as absent, low (4 DNA copies), moderate (104–108 DNA copies) or high-level (108–1011 DNA copies). Participants kept detailed diaries regarding sexual behaviour, menstruation, antibiotic use and vulvovaginal symptoms. Results: We noted three states of the vaginal microbiota: three women had high-level lactobacilli with intermittent, transient low-level G. vaginalis throughout the sampling period (State 1); five women had high-level lactobacilli with persistent, fluctuating low to moderate-level G. vaginalis and other BV associated anaerobic species throughout the sampling period (State 2); two women had polymicrobial colonisation with high-level G. vaginalis and other BV associated species, and intermittent, transient low-level, or persistent moderate-level Lactobacillus jensenii and crispatus throughout the sampling period (State 3). Ten women shifted between States 2 and 3 on at least one occasion. Extremely rapid transition from State 2 to 3 over. Conclusions: The vaginal microbiota is extremely dynamic and BV develops over narrow time intervals. Low-levels of BV associated species in the vagina may be a risk factor for rapid, incident BV. Future studies will identify drivers of shifts in the vaginal bacterial biota.